Bottomonium above deconfinement in lattice nonrelativistic QCD - RYAN, SINEAD MARIE (American Physical Society, 2011)
We study the temperature dependence of bottomonium for temperatures in the range 0.4Tc<T<2.1Tc, using nonrelativistic dynamics for the bottom quark and full relativistic lattice QCD simulations for Nf=2 light flavors on a highly anisotropic lattice. We find that the ? is insensitive to the temperature in this range, while the ?b propagators show a crossover from the exponential decay characterizing the hadronic phase to a power-law behavior consistent with nearly free dynamics at T?2Tc
PUBLISHED
Keywords: Particles and fields physics; bottomonium